The Icarus Flight of Perinatal Stem and Renal Progenitor Cells Within Immune System - Picerno, Angela; Castellano, Giuseppe; Curci, Claudia; Kopaczka, Katarzyna; Stasi, Alessandra; Pertosa, Giovanni Battista; Sabbà, Carlo; Gesualdo, Loreto; Gramignoli, Roberto; Sallustio, Fabio (Frontiers in Immunology, 2022)
Our immune system actively fights bacteria and viruses, and it must strike a delicate balance between over- and under-reaction, just like Daedalus and Icarus in Greek mythology, who could not escape their imprisonment by flying too high or too low. Both human amniotic epithelial and mesenchymal stromal cells and the conditioned medium generated from their culture exert multiple immunosuppressive activities. They have strong immunomodulatory properties that are influenced by the types and intensity of inflammatory stimuli present in the microenvironment. Notably, very recently, the immunomodulatory activity of human adult renal stem/progenitor cells (ARPCs) has been discovered. ARPCs cause a decrease in Tregs and CD3+ CD4- CD8- (DN) T cells in the early stages of inflammation, encouraging inflammation, and an increase in the late stages of inflammation, favoring inflammation quenching. If the inflammatory trigger continues, however, ARPCs cause a further increase in DN T cells to avoid the development of a harmful inflammatory state. As in the flight of Daedalus and Icarus, who could not fly too high or too low to not destroy their wings by the sun's heat or the sea's humidity, in response to an inflammatory environment, stem cells seem to behave by paying attention to regulating T cells in the balance between immune tolerance and autoimmunity. Recognizing the existence of both suppressive and stimulatory properties, as well as the mechanisms that underpin the immune reaction's duality, will aid in the development of active immunotherapeutic approaches that manipulate the immune system to achieve therapeutic benefit.